Helping Children Develop Knowledge of Audience and Purpose of Their Writing - Utami Widiati (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1998)
When writing, children should understand how knowledge of audience and purpose influences writing: the range of types of writing will vary according to the audience and the particular purpose. Unfortunately, many children seem to think that the teacher is the sole audience for classroom writing with the purpose of transmitting information or conveying ideas to the teacher for appraisal. This article highlights the importance of knowing audience and purpose when writing and the teachers’ role in a classroom context in helping children develop knowledge of audience and purpose by applying some possible writing activities in the classroom.